Teachers’ Roles and Teaching Styles - Hearn, Izabella (My University, 2014)
Whatever we teach, whatever we hope the students are going to learn, the experience is richer, more memorable and more motivating when we engage the emotions, and when we include an element of fun. In this session we are going to explore how the teacher can influence the dynamics of the classroom and bring out the best in each student. All learners learn differently but they all need to believe in their ability to succeed, they need to feel confident to ask questions, they need to know that the teacher is there to support them and that they belong to a harmonious group where there is mutual support and rapport. In order to reach all our students successfully, we need to become multisensory, to assess our own way of experiencing the world, so that we can use our strengths effectively and work on our weaker areas. Finally we shall address the need for teachers to create a balance between the role of guide/facilitator and that of an “authority” within the classroom.
Keywords: Didáctica; Teacher style role